Efikasi diri sebagai mediator antara strength-based parenting dan academic buoyancy pada masa pandemi COVID-19 - Chairina, Anindita; Primana, Linda (Persona:Jurnal Psikologi Indonesia, 2021)
Abstract To overcome adversities during Pembelajaran Jarak Jauh or long-distance learning, students need to develop academic buoyancy, described as ‘the ability to deal with daily academic setbacks and challenges. Parents’ role during PJJ is important since students spend more time at home. This study aims to investigates the relationship between strength-based parenting and academic buoyancy through academic self-efficacy, social self-efficacy, and emotional self-efficacy. 238 high school students in Indonesia participated in this study. Strength-Based Parenting Scale (α=0,941), Self-Efficacy Questionnaire for Children [α=0,790 (akademik), α=0,774 (sosial), α=0,817 (emosional)], and Academic Buoyancy Scale (α=0,564) were used to measure the variables. The results showed that academic self-efficacy and emotional self-efficacy serve as unique mediators in the relationship between SBP and academic buoyancy. Meanwhile, the role of social self-efficacy as a mediator is not significant. When parents identify and cultivate their children’s strengths, children will believe in their ability to carry out academic tasks and deal with negative emotions, which in turn help them overcome setbacks and challenges during PJJ. Keywords: Academic buoyancy; academic self-efficacy; emotional self-efficacy; social self-efficacy; strength-based parenting Abstrak Dalam menghadapi tantangan selama proses Pembelajaran Jarak Jauh (PJJ) dalam masa Pandemi Covid-19, peserta didik perlu mengembangkan academic buoyancy, yaitu kemampuan untuk mengatasi kemunduran dan tantangan akademis sehari-hari. Peran orang tua selama pandemi menjadi penting karena peserta didik lebih banyak menghabiskan waktu di rumah. Penelitian ini bertujuan untuk mengetahui apakah strength-based parenting, sebuah pendekatan pengasuhan yang menekankan pada identifikasi dan pengembangan kekuatan anak, dapat memprediksi academic buoyancy melalui efikasi diri akademik, efikasi diri sosial, dan efikasi diri emosional. Penelitian melibatkan 238 peserta didik tingkat SMA di Indonesia melalui teknik convenience sampling. Alat ukur yang digunakan adalah Strength-Based Parenting Scale (α=0,941), Self-Efficacy Questionnaire for Children [α=0,790 (akademik), α=0,774 (sosial), α=0,817 (emosional)], dan Academic Buoyancy Scale (α=0,564). Hasil penelitian menunjukkan bahwa efikasi diri akademik dan efikasi diri emosional masing-masing memediasi hubungan antara SBP dan academic buoyancy secara signifikan. Efikasi diri sosial tidak ditemukan memiliki peran mediasi. Ketika orang tua mengenali dan mengembangkan kekuatan yang peserta didik miliki, maka peserta didik akan yakin dengan kemampuannya untuk melakukan tugas akademis dan dapat mengatasi emosi negatifnya. Dengan demikian, peserta didik lebih mudah mengatasi kemunduran dan tantangan akademis yang dialami selama PJJ. Kata kunci: Academic buoyancy; efikasi diri akademik; efikasi diri emosional; efikasi diri sosial; strength-based parenting